Luminescent properties of fine-dispersed self-propagating high-temperature synthesized ZnS:Cu,Mg - Bacherikov, Yu.Yu.; Zhuk, A.G.; Kurichka, R.V.; Okhrimenko, O.B.; Gilchuk, A.V.; Shcherbyna, O.V.; Herkalyuk, M.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
The influence of magnesium impurities on the luminescent properties of ZnS:Cu,Mg obtained by self-propagating high-temperature synthesis (SHS) has been investigated. Special attention was paid to changes in photoluminescence spectra caused by relaxation processes in ZnS:Cu,Mg-SHS. It was shown that the introduction of magnesium into ZnS:Cu-SHS leads to a change in symmetry of the ZnS crystal lattice. It leads to relaxation, quenching the photoluminescence bands caused by the presence of copper impurities in ZnS.